Hollow mesoporous polydopamine nanospheres: synthesis, biocompatibility and drug delivery. (22nd April 2021) - Lin, Kunpeng; Gan, Ying; Zhu, Peide; Li, Shanshan; Lin, Chen; Yu, Shuling; Zhao, Shuang; Shi, Jiahua; Li, Runming; Yuan, Jinfang
Abstract: Various polydopamine (PDA) nanospheres were synthesized by utilizing triblock copolymer Pluronic F127 and 1, 3, 5-trimethylbenzene (TMB) as soft templates. Precise morphology control of polydopamine nanospheres was realized from solid polydopamine nanospheres to hollow polydopamine nanospheres, mesoporous polydopamine nanospheres and hollow mesoporous polydopamine nanospheres (H-MPDANSs) by adjusting the weight ratio of TMB to F127. The inner diameter of the prepared H-MPDANSs can be controlled in the range of 50–100 nm, and the outer diameter is about 180 nm. Furthermore, the thickness of hollow mesoporous spherical shell can be adjusted by changing the amount of dopamine (DA). The H-MPDANSs have good biocompatibility, excellent photothermal properties, high drug loading capacity, and outstanding sustainable drug release properties. In addition, both NIR laser irradiation and acid pH can facilitate the controlled release of doxorubicin (DOX) from H-MPDANSs@DOX.